Pelatihan Aplikasi Responsive Web dan Konten Web Dalam Pemrograman Web Multimedia - Supiyandi, Supiyandi; Lingga, Cindy Valentina; Firtiani, Ade Irda; Tanjung, Agung Hafizh; Malau, Sebastian Veron (LKP KARYA PRIMA KURSUS, 2024)
Training responsive web applications and web content in multimedia web programming, with a focus on case studies at SMK Telkom 1 Field. Learning multimedia web programming has become an important aspect of the educational curriculum in vocational secondary schools. The study aims to analyze the effectiveness of such training in improving students' skills in developing responsive web applications and generating quality web content. Data collection methods involve observations, interviews, and analysis of curriculum-related documents as well as training results. Research results show that training responsive web applications and web content makes a positive contribution in improving students' understanding and skills in multimedia web development. This research provides important insights for the development of educational curricula and implementation of more effective learning strategies in the field of multimedia web programming in secondary education institutions.